Association of Multiple Biomarkers With Risk of All-Cause and Cause-Specific Mortality After Acute Coronary Syndromes: A Secondary Analysis of the PLATO Biomarker Study - Lindholm, Daniel (JAMA Cardiol, 2018)
IMPORTANCE: Mortality remains at about 5% within a year after an acute coronary syndrome event. Prior studies have assessed biomarkers in relation to all-cause or cardiovascular deaths but not across multiple causes. OBJECTIVE: To assess if different biomarkers provide information about the risk for all-cause and cause-specific mortality. DESIGN, SETTING, AND PARTICIPANTS: The Platelet Inhibition and Patient Outcomes (PLATO) trial randomized 18 624 patients with acute coronary syndrome to ticagrelor or clopidogrel from October 2006 through July 2008. In this secondary analysis biomarker substudy, 17 095 patients participated. MAIN OUTCOMES AND MEASURES: Death due to myocardial infarction, heart failure, sudden cardiac death/arrhythmia, bleeding, procedures, other vascular causes, and nonvascular causes, as well as all-cause death. EXPOSURES: At baseline, levels of cystatin-C, growth differentiation factor-15 (GDF-15), high-sensitivity C-reactive protein, high-sensitivity troponin I and T, and N-terminal pro-B-type natriuretic peptide (NT-proBNP) were determined. RESULTS: The median (interquartile range) age of patients was 62.0 (54.0-71.0) years. Of 17 095 patients, 782 (4.6%) died during follow-up. The continuous associations between biomarkers and all-cause and cause-specific mortality were modeled using Cox models and presented as hazard ratio (HR) comparing the upper vs lower quartile. For all-cause mortality, NT-proBNP and GDF-15 were the strongest markers with adjusted HRs of 2.96 (95% CI, 2.33-3.76) and 2.65 (95% CI, 2.17-3.24), respectively. Concerning death due to heart failure, NT-proBNP was associated with an 8-fold and C-reactive protein, GDF-15, and cystatin-C, with a 3-fold increase in risk. Regarding sudden cardiac death/arrhythmia, NT-proBNP was associated with a 4-fold increased risk and GDF-15 with a doubling in risk. Growth differentiation factor-15 had the strongest associations with other vascular and nonvascular deaths and was possibly associated with death due to major bleeding (HR, 4.91; 95% CI, 1.39-17.43). CONCLUSIONS AND RELEVANCE: In patients with acute coronary syndrome, baseline levels of NT-proBNP and GDF-15 were strong markers associated with all-cause death based on their associations with death due to heart failure as well as due to arrhythmia and sudden cardiac death. Growth differentiation factor-15 had the strongest associations with death due to other vascular or nonvascular causes and possibly with death due to bleeding. TRIAL REGISTRATION: ClinicalTrials.gov Identifier: NCT00391872.